2009
DOI: 10.1016/j.foodres.2009.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidin content in foods is largely underestimated in the literature data: An approach to quantification of the missing proanthocyanidins

Abstract: a b s t r a c tThe content of proanthocyanidins (PA) in foods is usually determined by HPLC analysis of aqueousorganic extracts. However, the appreciable amounts of PA that remain in the residues of extraction usually are not considered for analysis. Attempts to determine these non-extractable proanthocyanidins (NEPA) by enzymatic-chemical methods have obtained partial results. The general aim of this work was the estimation of the total content of PA, including both extractable PA (EPA) and NEPA in some foods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 45 publications
5
113
3
2
Order By: Relevance
“…In the case of nonextractable PA, acid-catalyzed depolymerization in the presence of suitable nucleophilic reagents, such as benzylmercaptan, toluene-a-thiol (thiolysis) and phloroglucinol, or pectinolytic and cellulolytic enzymes to release PP from the food matrix, has been used as a preliminary step to HPLC analysis [21][22][23][24][25][26][27]. However, the PA contents reported in these studies were very low compared with the values reported after butanol/HCl/Fe extractions [28].…”
Section: Nepp In Plant-derived Foodsmentioning
confidence: 96%
“…In the case of nonextractable PA, acid-catalyzed depolymerization in the presence of suitable nucleophilic reagents, such as benzylmercaptan, toluene-a-thiol (thiolysis) and phloroglucinol, or pectinolytic and cellulolytic enzymes to release PP from the food matrix, has been used as a preliminary step to HPLC analysis [21][22][23][24][25][26][27]. However, the PA contents reported in these studies were very low compared with the values reported after butanol/HCl/Fe extractions [28].…”
Section: Nepp In Plant-derived Foodsmentioning
confidence: 96%
“…Nevertheless, the results constitute evidence of an appreciable presence of NEPP in plant foods and of their contribution to total polyphenol intake. (31) Quince 48 (32) Banana 980 (SD 45)* (27) Apple pomace 18 -23 (33) Cranberry pomace 1685 (34) Cocoa powder 602 (SD 13) (35) Carob pod 180 (36) Hydrolysable phenolics Onion 410 (SD 20)* (37) Black olive 14 -40 (38) Apple 78 (SD 6) (29) Medlar 0·5 -1·0 (39) Mandarin 39 -107 (40) Acerola 390 (SD 10)* (41) Cashew apple 1210 (SD 70)* † (41) Black currant pomace…”
Section: Occurrence Of Non-extractable Polyphenols In Dietsmentioning
confidence: 99%
“…The method by Porter, Hrstich, and Chan [16] and a modified one by Pérez-Jiménez, Arranz, and Saura-Calixto [17] were used during this study. For liquid cocoa extract suspected of having high reactivity, the following dilutions were made: 1:5, 1:10.…”
Section: Determination Of the Total Flavonoid Content (Tfc) Using Thementioning
confidence: 99%